Prevention of new-onset atrial fibrillation in elderly patients undergoing anatomic pulmonary resection by infusion of magnesium sulfate: protocol for a randomized controlled trial - Jin, Shuqing; An, Long; Chen, Linsong; Liu, Huqing; Chen, Hongfei; Lv, Xin (Frontiers in Cardiovascular Medicine, 2023)
Atrial fibrillation is the most commonly sustained arrhythmia after pulmonary resection, which has been shown to predict higher hospital morbidity and mortality.The lack of strong evidence-based medical evidence make doctors have very few options for medications to prevent new onset atrial fibrillation following thoracic surgery. Magnesium can prevent peri-operative atrial fibrillation in patients undergoing cardiac surgery, but this has not yet been fully studied in patients undergoing non-cardiac thoracic surgery, and therefore is the aim of this study. This is a single-center, prospective double blind randomized controlled trial. 838 eligible patients will be randomly assigned to one of two study groups: Control group or 2 Magnesium group. Patients in Magnesium group receive 80 mg magnesium sulfate/kg ideal weight in 100 ml normal saline 30 minutes preoperatively. Control Group receive same volumes of normal saline for the same time. The primary outcome is the incidence of new-onset AF intra-operative and on 1st, 2nd and 3rd postoperative days.The secondary outcomes will be bradycardia, hypertension, hypotension and flushing.It will also be recorded if stroke or any other type of arrhythmia occurs. Postoperative respiratory suppression and gastrointestinal discomfort, ICU stays and total duration of hospital stays, in-hospital mortality and 3-month all-cause mortality are also recorded as important outcomes. This study aims to prospectively evaluate the prophylactic effects of magnesium sulfate against atrial fibrillation compare with a placebo control group during and following anatomic pulmonary resection. The results may provide reliable evidence for prophylactic value of magnesium against atrial fibrillation in lung cancer patients. The trial was approved by the Clinical Research Ethics Committee of Shanghai Pulmonary Hospital and has been registered at Chinese Clinical Trial Registry (www. chictr.org.cn, identifier: ChiCTR2300068046).